Romero-Fresco, P. (2019). Accessible filmmaking: Integrating translation and accessibility into the filmmaking process. Routledge. 266 pp. - Remael, Aline (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Book review